On the Nature of Models: The Unfinished Debate - Jedlička, Petr (Teorie vědy / Theory of Science, 2017)
Book review: Ippoliti, Emiliano, Sterpetti, Fabio, Nickles Thomas (editors): Models and Inferences in Science (Switzerland: Springer International Publishing, 2016, 256 p.)